Scaling properties of delay times in one-dimensional random media - Bodyfelt JD; Méndez-Bermúdez JA; Chabanov A; Kottos T (My University)
The scaling properties of the inverse moments of Wigner delay times are investigated in finite one-dimensional (1D) random media with one channel attached to the boundary of the sample. We find that they follow a simple scaling law which is independent of the microscopic details of the random potential. Our theoretical considerations are confirmed numerically for systems as diverse as 1D disordered wires and optical lattices to microwave waveguides with correlated scatterers. © 2008 The American Physical Society.
Keywords: 02 Physical Sciences; 03 Chemical Sciences; 09 Engineering